Study of cytological findings of lymphocytic thyroiditis and its correlation with anti-thyroid peroxidase (anti-TPO) antibody levels and thyroid-stimulating hormone (TSH) levels: A retrospective observational study. - Pandey, Shreya; Dive, Prakash; Dr Sudhamani. S (Student's Journal of Health Research Africa, 2025)
Introduction: Lymphocytic thyroiditis is an autoimmune thyroid disorder marked by diffuse lymphocytic infiltration of the thyroid gland. It is the second most common thyroid pathology encountered on fine-needle aspiration cytology (FNAC), predominantly affecting women. The disorder presents with variable thyroid functional states, including hypothyroidism, euthyroidism, and hyperthyroidism. Objective: To evaluate the cytological spectrum of lymphocytic thyroiditis and to correlate cytological grades with serum Anti-thyroid peroxidase (anti-TPO) antibody titers and thyroid-stimulating hormone (TSH) levels. Materials and methods: A retrospective study was carried out over 30 months (2021–2023), including 44 FNAC-confirmed cases of lymphocytic thyroiditis. Cytological grading was performed using the system proposed by Bhatia et al., and correlation with Anti-TPO antibody levels and TSH values was assessed. Both parameters were measured using ADVIA Centaur XP immunoassay analyser employing chemiluminescent technology. Data were analysed with SPSS software, and statistical significance was set at p < 0.05. Results: Of the 44 cases, 39 were females (88.63%), with the 21–30 years age group being most commonly affected (29.5 %). Cytological grading revealed Grade I in 18 cases (40.9%), Grade II in 17 cases (38.63%), and Grade III in 9 cases (20.45%). Elevated Anti-TPO antibody levels were observed in 11 cases overall, with the highest frequency in Grade III (88.88%). Raised TSH levels were detected in 13 patients, more frequently in Grade II (58.82%). Correlation between cytological grades and biochemical markers was statistically significant (p < 0.05). Conclusion: Cytological grading in conjunction with biochemical evaluation provides a comprehensive assessment of lymphocytic thyroiditis, facilitating early diagnosis and appropriate management. Recommendations: Routine integration of FNAC grading with Anti-TPO and TSH estimation is recommended for timely diagnosis, monitoring, and individualized patient management.